ERS statement on obstructive sleep disordered breathing in 1- to 23-month-old children. Issue 6 (7th December 2017) - Kaditis, Athanasios G.; Alonso Alvarez, Maria Luz; Boudewyns, An; Abel, Francois; Alexopoulos, Emmanouel I.; Ersu, Refika; Joosten, Koen; Larramona, Helena; Miano, Silvia; Narang, Indra; Tan, Hui-Leng; Trang, Ha; et al.
The present statement was produced by a European Respiratory Society Task Force to summarise the evidence and current practice on the diagnosis and management of obstructive sleep disordered breathing (SDB) in children aged 1–23 months. A systematic literature search was completed and 159 articles were summarised to answer clinically relevant questions. SDB is suspected when symptoms or abnormalities related to upper airway obstruction are identified. Morbidity (pulmonary hypertension, growth delay, behavioural problems) and coexisting conditions (feeding difficulties, recurrent otitis media) may be present. SDB severity is measured objectively, preferably by polysomnography, or alternatively polygraphy or nocturnal oximetry. Children with apparent upper airway obstruction during wakefulness, those with abnormal sleep study in combination with SDB symptoms ( e.g. snoring) and/or conditions predisposing to SDB ( e.g. mandibular hypoplasia) as well as children with SDB and complex conditions ( e.g. Down syndrome, Prader–Willi syndrome) will benefit from treatment. Adenotonsillectomy and continuous positive airway pressure are the most frequently used treatment measures along with interventions targeting specific conditions ( e.g. supraglottoplasty for laryngomalacia or nasopharyngeal airway for mandibular hypoplasia). Hence, obstructive SDB in children aged 1–23 months is a multifactorial disorder that requires objective assessment and treatment of all underlying abnormalities that contribute to upper airway obstruction during sleep. Obstructive sleep disordered breathing in young children is a heterogeneous group of disorders http://ow.ly/qqgc30fGvaj